2016
DOI: 10.1038/ajg.2016.240
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Endoscopic Ultrasound-Based Approach to the Evaluation of Idiopathic Pancreatitis: Causes, Response to Therapy, and Long-term Outcome

Abstract: OBJECTIVES:Although idiopathic pancreatitis is common, the natural history is not well studied, and the best diagnostic approach to both single and multiple attacks remains undefi ned. METHODS:We prospectively evaluated patients with idiopathic pancreatitis over a 10-year period, and clinical information for each episode was reviewed. Endoscopic ultrasound (EUS) was performed in all patients. Patients with microlithiasis or bile duct stones were referred for cholecystectomy and endoscopic retrograde cholangiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 52 publications
2
40
0
Order By: Relevance
“…Considering relapsing AP, we found an overall recurrence of 27.4%, with the highest proportion in patients with multiple attacks (57.1%) and in patients with a previous cholecystectomy (46.4%). These results are similar to those of previous studies, which found relapsing rates of 11-32% after a first episode when the cause was not identified and treated [26,27], and in which recurrence rates were higher in patients with multiple attacks than in those with a single episode [28]. In this setting, we found a group of patients with a first episode of AP, a high proportion of intact gallbladder and biliary disease, mainly stones.…”
Section: Discussionsupporting
confidence: 91%
“…Considering relapsing AP, we found an overall recurrence of 27.4%, with the highest proportion in patients with multiple attacks (57.1%) and in patients with a previous cholecystectomy (46.4%). These results are similar to those of previous studies, which found relapsing rates of 11-32% after a first episode when the cause was not identified and treated [26,27], and in which recurrence rates were higher in patients with multiple attacks than in those with a single episode [28]. In this setting, we found a group of patients with a first episode of AP, a high proportion of intact gallbladder and biliary disease, mainly stones.…”
Section: Discussionsupporting
confidence: 91%
“…Both EUS and MRCP are useful techniques in the etiologic diagnosis of IAP patients, and intravenous secretin combined with MRCP or EUS not only enhances the pancreatic duct morphology but also provides indirect functional information with which to investigate sphincter of Oddi dysfunction. 19 Overall, many studies showed that EUS has a higher diagnostic yield than MRCP in idiopathic pancreatitis 5,24 because of its high accuracy in recognizing biliary disease, especially in patients who have not had a cholecystectomy. 18 Some studies suggested that EUS should be considered first for idiopathic pancreatitis after failure of conventional radiography.…”
Section: Discussionmentioning
confidence: 99%
“…In cases where PAB remains suspected or in which other causes for BP have been excluded, endoscopic ultrasonography, which has greater sensitivity for the diagnosis of microcapsules (less than 5 mm), may be requested. A study showed that 2/3rd of patients previously diagnosed as idiopathic had biliary etiology confirmed after endoscopic ultrasonography [31,32].…”
Section: Biliary Causesmentioning
confidence: 99%